Relation between EEG activity and brain oxygenation in preterm neonates (2017)
This study investigates the relationship between brain oxygenation, assessed by means of near infrared spectroscopy (NIRS), and brain function, assessed by means of electroencephalography (EEG). Using NIRS signals measuring the regional cerebral oxygen saturation (rScO2) and computing the fractional tissue oxygen extraction (FTOE), we compared how these variables relate to different features extracted from the EEG, such as the inter-burst interval (IBI) duration and amplitude, the amplitude of the EEG, and the amplitude of the burst. A cohort of 22 neonates undergoing sedation by propofol was studied and a regression of the NIRS-derived values to the different EEG features was made. We found that higher values of FTOE were related to higher values of EEG amplitude. These results might be of used in the monitoring of proper brain function in neonates.